THE INFLUENCE OF PROMOTION AND PRODUCT QUALITY ON CUSTOMER LOYALTY THROUGH PURCHASING DECISIONS AS AN INTERVENING VARIABLE - Sopyan Ibnu Hasim; Antong; Syafruddin; Muammar Khaddapi (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
This study aims to analyze the influence of promotion and product quality on customer loyalty with purchase decisions as an intervening variable in the Teras Coffee micro business in Watampanua Village, Angkona District, East Luwu. This research method uses a quantitative approach with data collection through a questionnaire filled out by 100 respondents. The results show that product promotion and quality have a significant influence on purchasing decisions, which in turn affects customer loyalty. However, it was found that product promotion and quality did not have a significant direct influence on customer loyalty without going through the purchase decision. These findings suggest that purchase decisions play an important role in building customer loyalty, indicating that efforts to increase customer loyalty cannot rely solely on product quality and promotional strategies, but must also ensure that consumers are satisfied with their purchase decisions. As such, effective product promotion and quality improvement strategies must be balanced with efforts to improve the buying experience to achieve sustainable customer loyalty.